The costs and logistics of distributing ‘forest packs’ containing novel vector control tools to forest-exposed populations in Cambodia - Joshua Yukich; Dyna Doum; David J. McIver; Jason H. Richardson; Siv Sovannaroth; Neil F. Lobo; Allison Tatarsky (Malaria Journal)
Abstract Background Malaria incidence in the Greater Mekong Subregion has been on the decline, and most remaining malaria risk in the region is concentrated among hard-to-reach populations, especially those with exposure to forested areas. New vector control tools focused on outdoor protection in forest settings are needed for these populations. Methods The delivery of a ‘forest pack’ containing a volatile pyrethroid spatial repellent (VPSR), a topical repellent, and pyrethroid treatment of clothing was evaluated in an operational study in Cambodia. Costs were collected using micro-costing approaches and the cost of distribution for the ‘forest pack’ was estimated using standard economic evaluation approaches and examined in sensitivity analyses. Results The cost per eligible person (the target population) per malaria season for the whole pack was estimated to be 138 USD, which was nearly entirely driven by the cost of the products. Conclusions Modifications to the ‘forest pack’ including adding a longer-lasting spatial repellent product or a reduced-cost topical repellent could significantly reduce the cost of pack distribution over the course of a malaria season.